Black holes and galaxy environment in cosmological simulations - Muldrew, Stuart I. (2013)
Understanding the formation and evolution of galaxies is one of the primary research goals of astronomy today. Galaxies are observed to have a range of masses, colours and morphologies, and various processes, including feedback, have been proposed to explain these differences. Some of these processes are related to the environment in which a galaxy resides. In this Thesis I present the results of three projects I have undertaken to help increase our understanding of galaxy formation. The first was to investigate the different methods of structure detection used in simulations. Placing an identical subhalo at different radii inside a larger halo demonstrated that subhalo mass recovery is radially dependent. Subhaloes closer to the centre of a halo are recovered smaller than haloes near the edge, but their peak circular velocity is less affected. The second project set about investigating different ways of measuring galaxy environment. Observationally galaxy environment is most commonly measured through nearest neighbours or fixed apertures, and these have different relationships to the underlying dark matter haloes. Fixed aperture measures are sensitive to halo mass and best probe the `large-scale environment' external to a halo. Meanwhile nearest neighbour measures are insensitive to halo mass and best probe the `local environment' internal to a halo. The final project involved implementing the Accretion Disc Particle (ADP) model of black hole growth within a cosmological, large volume simulation, including cooling, star formation and feedback. Comparing this method with a modified Bondi-Hoyle model allows for the investigation of how accretion rates affect feedback and galaxy properties. ADP suffers from the limited resolution of large-scale simulations and produces unphysically large accretion discs. Both models can reproduce the local black hole scaling relations, but produce black hole mass functions that do not agree with observations.